Parámetros indicadores de valor nutritivo en cinco pastos tropicales en la época lluviosa en el trópico seco de Cota Rica - Arroyo, Rafael Angel (1997)
This essay was carried out in Hojancha, Guanacaste to evaluate the nutritive values of the following grasses: jaragua (Hyparrhenia rufa) (Nees), african star grass (Cynodon nlenfuensis) (L)(Pers), transvala (Digitaria decumbens) veranero (Andropogon gayanus)(Kunth) y congo (Brachiaria ruziziensis)(Germain et Everard), under three cut intervals (28, 35 and 42 days).The evaluated variables were: Dry Matter Production (DMP, kg/ha/cut), In vitro Dry Matter Digestibility (IVDMD, %), Digestible Dry Matter (DDM, kg/ha/cut), Crude Protein Content (CP, %), Crude protein production (CPP, kg/ha/cut), Digestible Crude Protein Production (DCPP, kg/ha/cut), Ruminal Dry Matter Disappeareance (RDMD, %/hour), Ruminal Dry Matter Disappeareance Mean Time (RDMDMT, hours).The largest DMP was found for the veranero grass at 28 and 35 day intervals (1527,5 and 2424,4 kg/ha/cut) while at the 42 day interval the congo grass (2886,8 kg/ha/cut) had the largest DMP, followed by veranero grass with 2705,0 kg/ha/cut).The veranero and transvala grasses showed the highest RDMD and RDMDMT as compared to the other grasses in the study, as a consequence of their better chemical composition. Between the jaragua and veranero grasses there were no differences with respect to their chemical composition and ruminal characteristics. The poorest DMP, chemical composition (excluding CP) and RDMD was shown by the african star grass.